2013
DOI: 10.1007/s11274-013-1531-x
|View full text |Cite
|
Sign up to set email alerts
|

A new antibacterial amino phenyl pyrrolidone derivative from a novel marine gliding bacterium Rapidithrix thailandica

Abstract: A recently described marine gliding bacterium Rapidithrix thailandica strain TISTR 1741 was isolated from biofilm specimen collected from the Andaman Sea in Thailand. Four liters fermentation broth of R. thailandica TISTR 1741 cultivated in VY/2 medium were extracted with methanol to yield a novel amino phenyl pyrrolidone derivative compound (1) with antibacterial activities. The chemical structure and physico-chemical properties of 1 were investigated by spectrometry techniques. Compound 1 exhibited selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In 2009, iso-α-cyclopiazonic acid (213), along with its isomer 210, was structurally characterized in the marine algae-derived A. flavus C-F-3 [169], the marine prawn-derived A. flavus OUCMDZ-2205 [170], and marine-derived P. camemberti [171]. Two new CPA derivatives, amycocyclopiazonic acid (214) and amycolactam (215), were isolated from a sponge-associated rare actinomycete Amycolatopsis sp.…”
Section: α-Cyclopiazonic Acid (Cpa)-type Tetramic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, iso-α-cyclopiazonic acid (213), along with its isomer 210, was structurally characterized in the marine algae-derived A. flavus C-F-3 [169], the marine prawn-derived A. flavus OUCMDZ-2205 [170], and marine-derived P. camemberti [171]. Two new CPA derivatives, amycocyclopiazonic acid (214) and amycolactam (215), were isolated from a sponge-associated rare actinomycete Amycolatopsis sp.…”
Section: α-Cyclopiazonic Acid (Cpa)-type Tetramic Acidsmentioning
confidence: 99%
“…The bioassay results showed that 210 has potent toxicity toward brine shrimp (IC 50 < 1.0 µg/mL) [181] and cytotoxicity against four HTCLs (IC 50 = 2.4-21.5 µM) [169] as well as antibacterial activity against E. coli [184]. However, its isomer (213)…”
Section: α-Cyclopiazonic Acid (Cpa)-type Tetramic Acidsmentioning
confidence: 99%
“…Each gliding bacterial isolate was cultivated in a 250 ml Erlenmeyer flask containing 100 ml of SAP2 broth medium and 2 g of amberlite XAD-16 resins (Sangnoi et al 2008, 2009, 2014; Spyere et al 2003). The cultivation flasks were incubated and shaken at 200 rpm for 7 days at 25 °C.…”
Section: S Rrna Gene Sequence and Phylogenetic Analysismentioning
confidence: 99%
“…The resins were collected using a nylon mesh and rinsed with deionized water to remove unwanted cells and other contaminants. Resins were left to dry at room temperature for 15 min and also soaked in 100 ml methanol for 1 h. Methanolic phases were separated from the resins, and methanolic crude extracts were obtained after evaporating a methanol solvent (Sangnoi et al 2008, 2009, 2014). Crude extracts were prepared to a final concentration of 25 mg/ml in DMSO.…”
Section: S Rrna Gene Sequence and Phylogenetic Analysismentioning
confidence: 99%
“…Pyrrolidinone derivatives are widely known for their biological activities such as antimicrobial [1], antiviral [2], etc. Furthermore, thiazole is an important pharmacophore associated with varied biological activities including antimicrobial [3], antiviral [4].…”
Section: Introductionmentioning
confidence: 99%